Sizzle [compact disc, unabridged] : a novel - Garwood, Julie (Random House Audio, 2009)
After she accidentally captures a disturbing crime on camera, L.A. film student Lyra Prescott finds her final project for school changing from a documentary film into a work of horror. Terrified, Lyra turns to one of her best friend's many connections: sexy FBI agent Sam Kincaid. As the two work together to end the horror enveloping Lyra's life, they find their attraction for each other intensifying.